Regulating cell morphology of poly (lactic acid) foams from microcellular to nanocellular by crystal nucleating agent. (October 2022) - Wu, Ying; Zhang, Shuo; Han, Shuqing; Yu, Kesong; Wang, Linyan
Highlights: Fabrication of PLA foams with controllable cell structures and high compression property. The interaction mechanism between crystallization and foaming was analyzed systemically. The cell size transforms from mircoscale to nanoscale, and the cell number density increases by 5 orders of magnitude. The uniform pentagonal shape cells emerge in the PLA/TMC foams. The compressive strength of PLA/TMC foams increases from 0.76 MPa to 29.81 MPa at 108 ℃. Abstract: The inherent shortcomings of poor melt strength and crystallization behavior constrain the foamability and mechanical properties of poly (lactic acid) (PLA). In this work, a crystal nucleating agent was introduced into PLA system to solve the aforementioned issues by manipulating crystallization process. Isothermal crystallization results implied that the crystal nucleating agent promoted PLA crystallization greatly, where the adjusted ranges of crystallization rate and crystallinity were expanded obviously. Results indicated that the modified PLA foams displayed a mixed distribution of nanoscale and microscale cells at low temperatures, while the uniform pentagonal shape cells emerged in the foams prepared at 112 ℃. Accordingly, the cell size decreased from 44.62 μm to 360 nm, and the cell density increased from 9.06×10 8 cells/cm 3 to 7.48×10 13 cells/cm 3 . Moreover, the compressive strength of the modified foams was enhanced notably than that of pure PLA foams. Overall, the crystallization and foaming properties of PLA were analyzed systematically, the foaming properties were improved significantly by controlling proper crystallization, and this work would provide a prospective strategy to fabricate high performance PLA foams with controllable cell structures and high compression properties. Graphical abstract: Image, graphical abstract